Meningioma involving the superior sagittal sinus: long-term outcome after robotic radiosurgery in primary and recurrent situation - Schmutzer, Michael; Skrap, Benjamin; Thorsteinsdottir, Jun; Fürweger, Christoph; Muacevic, Alexander; Schichor, Christian (Frontiers in Oncology, 2023)
Treatment for meningiomas involving the superior sagittal sinus (SSS) is challenging and proved to be associated with higher risks compared to other brain locations. Therapeutical strategies either may be microsurgical (sub-)total resection but also adjuvant radiation or a combination of both.Thrombosis or SSS occlusion following resection or radiosurgery need to be further elucidated to assess, whether single or combined treatment is superior. We here present tumor control and side effect data of robotic radiosurgery (RRS) in combination with/ without microsurgery.From our prospective database we identified 137 patients with WHO grade I meningioma involving the SSS consecutively treated between 2005 and 2020. Treatment decisions were interdisciplinary.Patients either underwent RRS as initial/solitary treatment (group 1), as adjuvant treatment after subtotal resection (group 2) or due to recurrent tumor growth after preceding microsurgery (group 3). Positive tumor response was assessed by MRI and defined as reduction of more than 50% of volume. Study endpoints were time to recurrence (TTR), time to RRS, risk factors for decreased survival and side effects. Overall and specific recurrence rates for treatment groups were analyzed.Side effect data included therapy-related morbidity during follow-up (FU).137 patients (median age 58.3 years) with SSS meningiomas WHO grade I were analyzed: 51 patients (37.2%) in group 1, 15 patients (11.0%) in group 2 and 71 patients (51.8%) in group 3.Positive MR-morphological response to therapy was achieved in 50 patients (36.4%), no response was observed in 25 (18.2%) and radiological tumor progression was detected in 8 patients (5.8%).Overall 5-year probability of tumor recurrence was 15.8% (median TTR 41.6 months). 5-year probabilities of recurrence were 0%, 8.3.% and 21.5% for groups 1-3 (p=0.06). In multivariate analysis tumor volume was significantly associated with extent of SSS occlusion (p=0.026) and sex (p=0.011). Tumor volume significantly correlated with TTR (p=0.0046). Acute sinus venous thrombosis or venous congestion associated bleedings did not occur in any of the groups.3 RRS for grade I meningiomas with SSS involvement represents a good option as first line treatment, occasionally also in recurrent and adjuvant scenarios as part of a multimodal treatment strategy.